The Effectiveness of Horticulture Guiding Book for Improving Vocational Skills of Hearing Impairment Childen in SMALB - Dinda Ayu Maulida; Abdul Huda (Department of Special Education, 2019)
Effectiveness of the Horticulture Cultivation Handbook to Improve Vocational Skills of Hearing Impairment Children at SMALB. This study aims to determine the effectiveness of horticulture cultivation guidebooks to improve vocational skills of hearing impairment children. This research design uses development research. Data were analyzed by the design of one group pretest and posttest, and descriptive. The results showed that the horticulture cultivation manual was effective for improving vocational skills of hearing impairment children.